Peran Inklusi Keuangan Syariah terhadap Perkembangan UMKM di Kabupaten Sumenep (Studi pada BPRS Bhakti Sumekar) - Angraini, Yeni; Zakik (Universitas Airlangga, 2024)
This research is intended to identify and evaluate the contribution of Sharia financial inclusion at Sharia People's Financing Bank Bhakti Sumekar to the development of MSMEs in Sumenep Regency with the dimensions of accessibility, use of products and services, and service quality. This study determined sample size followed the Roscoe formula. At least 40 MSMEs were customers of Sharia People's Financing Bank Bhakti Sumekar were obtained. To collect data, a combination of interview methods and questionnaire distribution were used. The data was analyzed using SPSS for instrument testing, descriptive statistics, multiple linear regression, classical assumption testing, and hypothesis testing. Results showed that simultaneously, the variables of accessibility, use of products and services, and service quality have a significant impact on the development of MSMEs. However, partial use of products and services does not have a big impact on the development of MSMEs. This is partly due to the limited public awareness regarding Sharia financing, as well as the frequent misuse of credit financing. The implications of this research can provide direct benefits of Islamic financial inclusion, such as easier access to financing, better financial management, and increased business capacity. This will ultimately contribute to improved MSME performance, regional economic growth, and community welfare.